University management solutions during the COVID-19 pandemic: a case study of Lithuania - Navickienė, Vida; Droessiger, Gražina; Valantinaitė, Ilona; Trinkūnas, Vaidotas; Jaras, Arūnas (Business, Management and Economics Engineering, 2021)
Purpose – The article is aimed at analyzing university management decisions during the COVID-19 pandemic thus emphasizing the impact of the decisions made on the effective management of the situation.Research methodology – To achieve the established goal, research methodology involved the qualitative research strategy applying the semi-structured interview method and scientific literature analysis. The article is of a theoretical and empirical nature. The empirical part presents its individual research on implementing strategies in the field of adapting appropriate areas of the University as an important part of the study implementation process. The study involved 15 experts – 12 men and 4 women. The research results are the basis for developing practical guidelines for higher education institutions.Findings – Research findings have disclosed that successful management decisions fall into eight categories: management actions, the collaboration between the different levels of authorities and the academic community, the development and maintenance of a technical base, timely and continuous academic support for teaching staff, multipurpose support for students, control over the studying process, security assurance, solutions at the level of study programs. The article demonstrates a holistic approach to making the required decisions.Research limitations – Research limitations impose conducting a study in a specific culture and the organizational context of Lithuania.Practical implications – Practical implications suggest that the conducted research helps the leaders of various levels at educational establishments make the most useful necessary decisions for the institution in an emergency.Originality/Value – The uniqueness of the conducted research lies in the first attempt to show management solutions worked out by the universities in Lithuania during the COVID-19 pandemic.